EFFECT OF MULTIPLE MATING ON REPRODUCTIVE RATE IN THREEPOPULAR RACES OF SILKWORM Bombyx mori L. - Raju, P.J.; Mahadevappa; Guruswamy, D.; Raghuraman, R.; Dandin, S.B. (Annals of Tropical Research, 1996)
Economics of egg production is vital for grainages since it is a commercial preposition which necessitates recovery of maximum number of layings with high fecundity. Attempts have been made to increase reproductive rate by multiple mating in Pure Mysore (PM), a multivoltine race and Kalimpong-A (KA) and N4D2, the bivoltine races of silkworm Bombyx mori L. The studies revealed increase in egg laying coefficient for multiple-mated moths of all three races. The possible mechanism in multiple mating which stimulates oogenesis and thereby reproductive rate is discussed.